CULTIVATING COMPASSIONATE CHARACTER THROUGH THE LOVE CURRICULUM: A LITERATURE REVIEW ON STUDENT CHARACTER FORMATION AND TEACHER–STUDENT RELATIONSHIPS - Siti Muhibah; Julia Adelina; Al-Amin (International Journal of Teaching and Learning, 2026)
This study aims to examine the implementation of the Love Curriculum in shaping students' compassionate character and its impact on harmonious relationships between educators and learners, using a literature review approach. The growing moral crisis, emotional disengagement, bullying, intolerance, and weakening interpersonal relationships in contemporary educational environments have heightened the urgency of developing humanistic, compassion-based educational approaches. The Love Curriculum emphasizes values such as empathy, care, respect, compassion, and emotional connectedness as central foundations of the learning process. This study employed a qualitative library research method by analyzing scientific articles, books, policy reports, and reputable international publications indexed in Scopus and other academic databases published within the last five years. Data were collected through documentation techniques and analyzed using thematic content analysis to identify major concepts, educational strategies, benefits, and challenges related to compassion-based education. The findings revealed that the Love Curriculum significantly contributes to students’ character formation by strengthening empathy, emotional intelligence, social responsibility, ethical awareness, and prosocial behavior. Furthermore, harmonious teacher–student relationships characterized by trust, emotional support, and mutual respect positively influence students’ academic engagement and psychological well-being. However, the implementation of the Love Curriculum still faces several challenges, including the dominance of cognitive-oriented educational systems, limited teacher competence in compassionate pedagogy, and the impact of digital transformation on interpersonal interaction. This study concludes that the Love Curriculum represents an important framework for promoting holistic, humanistic, and transformative education in the twenty-first century. The study also recommends the integration of compassion-based values into curriculum development, teacher training, and school culture to create inclusive and emotionally supportive educational environments.